Navigating the 'inter' in intercultural education. Issue 1 (2nd January 2018) - Salter, Peta; Maxwell, Jacinta
ABSTRACT: The structure of the Australian national curriculum encompasses engagement with 'intercultural education'. Significantly, the context from which the curriculum was developed was heavily influenced by a multiculturalist ideology in which notions of cohesion and harmony were dominant. Therefore, those working with the curriculum need to understand the limited ways in which ideas of 'diverse' culture might be constructed. As a cultural text this curriculum is a place of encounter between teachers and the various influences on the curriculum document itself. We assert that the perpetuation of ideographs in the context and text of the curriculum, underpin how 'intercultural understanding' is positioned in the Australian Curriculum, and limit the narrative possibility of this encounter. It is essential to identify and interrogate such ideographs if we are to be cognisant of the complex politics of national curriculums and opportunities to 're-open' the place for encounter.